Team Avatar tales - Scheidt, Dave; Yang, Gene Luen; Hughes, Kiku; Koertge, Ronald; Goetter, Sara; McNeil, Carla Speed; Yovaniniz, Coni; Hicks, Faith Erin; Hill, Ryan, (Colorist); Little Corvus; Yang, Gene Luen; Scheidt, Dave; et al. (Milwaukie, OR : Dark Horse Books, 2019)
Gathers eight tales featuring the characters from the television program "Avatar, the Last Airbender" as they search for snacks, handle a prejudiced seashell dealer, and come to the aid of those who need their magical and martial arts skills.
Rebound / written by Gene Luen Yang ; illustrated by Ryan Hill -- The substitute / written by Dave Scheidt ; illustrated and lettered by Little Corvus -- Shells / written by Gene Luen Yang ; illustrated by Faith Erin Hicks -- Sokka's poem / written by Ron Koertge ; illustrated and lettered by Gene Luen Yang -- Toph and the boulder / written, illustrated, and lettered by Sara Goetter -- Origami / written, illustrated, and lettered by Kiku Hughes -- Sisters / written by Gene Luen Yang ; illustrated by Carla Speed McNeil -- The scarecrow / written by Dave Scheidt ; illustrated and lettered by Coni Yovaniniz.
At head of title: Nickelodeon Avatar, the last airbender.
Chiefly illustrations.
Keywords: Magic -- Fiction; Martial arts -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Cartoons and comics; Comic books, strips, etc